Non-invasive monitoring of microbial triterpenoid production using nonlinear microscopy techniques - Dianat, Mariam; Münchberg, Ute; Blank, Lars M.; Freier, Erik; Ebert, Birgitta E. (Frontiers in Bioengineering and Biotechnology, 2023)
Bioproduction of plant-derived triterpenoids in recombinant microbes is receiving great attention to make these biologically active compounds industrially accessible as nutraceuticals, pharmaceutics, and cosmetic ingredients. So far, there is no direct method for detecting triterpenoids under physiological conditions on a cellular level, information yet highly relevant to rationalizing microbial engineering. Here, we show in a proof of concept study that the combination of coherent anti-Stokes Raman scattering (CARS) and second-harmonic-generation (SHG) microscopy techniques can be applied for non-invasive monitoring of triterpenoid synthesis in both fixed yeast cells and cells growing in liquid culture. We show that the SHG signal in triterpenoid-producing strains is significantly higher than in a non-producing reference strain, correlating with lipophile content as determined by classical Nile red staining. In growing cultures, both CARS and SHG signals showed changes over time, enabling new insights into the dynamics of triterpenoid production and storage inside cells.